Influence of hydrogel use on soybean cultivation hydrical stress (Bioscience Journal, 2018)
Among the agricultural production factors, the water deficit is one of the main reasons that limits soy production in Brazil. In order to mitigate losses due to water stress in the plants, hydrogels appear as soil water conditioners. They are polymers capable of absorbing large amounts of water and are being used as a viable alternative to improve the storage of water in areas of scarcity. Hydrogen concentrations between 14 and 18 kg ha-1 resulted in higher plant height, number of pods, one hundred grain mass and grain yield.